Analisis Persepsi Maslahah Dalam Melakukan Pembelian Kompulsif - Sa'diah, Zulfatus; Maranti, Safika; Retnowati, May Shinta (JESI (Jurnal Ekonomi Syariah Indonesia), 2021)
Abstract            This study aims to determine the effect of the perception of maslahah on compulsive buying behavior This research is a quantitative research by integrating the dimensions of maslahah perception into the Theory of Planned Behavior (TPB) model. TPB is an integrated model that consists of four predictors of behavior, namely attitudes, subjective norms, perceived behavioral control (PBC), and intentions to behave. Sampling using Purposive Sampling, that is 200 respondents. To measure the variables using the Continuous rate scale.  While the data analysis technique used in this research is path analysis using Smart PLS 2.0 (Partial Least Square) software. The results of the study said that the maslahah perception construct had a significant effect on the attitude construct even though it was weak at 5.5%. Which means there are still about 94.5% of the attitude variables are influenced by other factors. Then the attitude construct has a significant effect on the compulsive buying behavior construct of 47.6%, which means that there are still around 52.4% of the variable Compulsive Buying Behavior which can be explained from other factors. While the construct of subjective norms and behavioral control has no effect on compulsive buying behavior. The reason for the rejection of these two hypotheses is thought to be because Muslim communities who have high subjective norms and behavioral control do not change their behavior in compulsive buying to be higher.Keywords: Maslahah, Compulsive Buying, Theory of Planned Behaviour